DIMENSI MUTU PRODUK BALAI LATIHAN PENDIDIKAN TEKNIK (BLPT) KAATEN TOMOHON - Meyriska Christi Howan; Paulus A. Pangemanan; Leonardus R. Rengkung (Sam Ratulangi University, 2017)
The research showed that the process of measuring the dimensions of product quality in Technical Education and Training Center (BLPT) Kaaten reached the total 2569 data retrieval scores indicating the index number of consumer satisfaction measurements of 85,63% and quite satisfied. This indicates that consumers who buy products at BLPT Kaaten Tomohon are aware of the benefits of BLPT products in terms of product quality dimensions that can be seen from the 8 dimensions of quality, namely performance, features, reliability, suitability, durability, ease of improvement, beauty and perception of quality. The measurement of quality dimension product of BLPT Kaaten Tomohon can be a reference for BLPT Kaaten Tomohon to continuously improve product quality in order to remain competitive in the market.